Copalyl Diphosphate Synthase Mutation Improved Salt Tolerance in Maize (Zea mays. L) via Enhancing Vacuolar Na+ Sequestration and Maintaining ROS Homeostasis - Zhang, Yushi; Wang, Yubin; Xing, Jiapeng; Wan, Jiachi; Wang, Xilei; Zhang, Juan; Wang, Xiaodong; Li, Zhaohu; Zhang, Mingcai (Frontiers in Plant Science, 2020)
Salinity stress impairs plant growth and causes crops yield losses worldwide. Reduction of in vivo gibberellin acids (GA) level is known to repress plant size but is beneficial to plant salt tolerance. However, the mechanisms of in vivo GA deficiency enhanced salt tolerance in maize is still ambiguous. In this study, we generated a maize mutant of ent-copalyl diphosphate synthase (one of the key enzyme for early steps of GA biosynthesis), zmcps, to explore the role of GA in maize salt tolerance. The typical dwarf phenotype with lower GAs content and delayed leaf senescence under salinity was observed in the zmcps plant. The leaf water potential and cell turgor potential were significant higher in zmcps than in wild-type under salt stress. The zmcps plants exhibited lower superoxide anion production rate in leaves and also the downregulated relative expression level of NAPDH oxidase ZmRbohA-C than the wild type maize under salt stress. Also, the zmcps plants had higher enzymatic activities of SOD and CAT and higher content of soluble sugars and proline under salt stress. The Na+/K+ ratio was not significantly different between zmcps and wild-type maize plants under salt stress condition, but the Na+ and K+ content were increased in zmcps leaves and shoots. Na+ fluorescent dye staining showed that zmcps leaves have significant higher vacuolar Na+ intensity than the wild-type maize. The expression level of vacuolar Na+/H+ exchanger gene ZmNHX1 and vacuolar proton pump genes ZmVP1-1 and ZmVP2 were upregulated in the zmcps plants under salinity, further proved that in vivo GA deficiency enhanced vacuolar Na+ sequestration in zmcps leaves cells to avoid Na+ cytotoxicity. Together, our results suggested that GA deficiency improved maize salt tolerance through maintaining ROS homeostasis and enhancing vacuolar Na+ sequestration.